Marketing Strategy in Enhancing Competitive Advantage at Mercure Chamonix Center Hotel, France - Kadek Sandita Nugraha; Ni Nyoman Sri Astuti; Ni Luh Eka Armoni (Journal of Applied Sciences in Travel and Hospitality, 2020)
The purpose of research was to develop a marketing strategy that can be applied to Mercure Chamonix Centre Hotel, France in enhancing the competitive advantage. This research is qualitative research through direct observation, interviews, and the study of literature. Data analysis performed by Internal External Factors, IE matrix analysis, SWOT analysis and QSPM. The result of analysis showed the position of Mercure Chamonix Centre Hotel, France in IE Matrix is in the fifth Cell with the total weight score for internal factor is 2.989 and the external factor with the score of 2.856. the position is on Growth (Concentration Through Horizontal Integration) or stability (there is no change). In SWOT Matrix, it can be defined to 5 strategies: SO (1. Add products, especially foods according to the origin of guest 2. Improving promotion techniques), WO (Adjust prices with competitors on similar products according to the perception of guest through social media), ST (Increase promotion by adding media channels) and WT (Improve employee performance on all lines through regular training).QSPM analysis shows that the strategy should be prioritized: (1) SO1 with the total TAS 6.61: (2) SO2 with the total TAS 5.73; (3) ST1 with the total TAS 4.26; (4) WO1 with the total TAS 4.60; (5) with the total TAS 4.20. Based on QSPM analysis it can be suggested the appropriate new marketing strategy for Mercure Chamonix Centre Hotel is Add products, especially foods according to the origin of guest.